A Spectral Rotary Analysis of Gravity Waves: An Application During One of the SOUTHTRAC Flights. Issue 1 (9th January 2023) - de la Torre, A.; Alexander, P.; Marcos, T.; Hierro, R.; Llamedo, P.; Hormaechea, J. L.; Preusse, P.; Geldenhuys, M.; Krasauskas, L.; Giez, A.; Kaifler, B.; Kaifler, N.; et al.
Abstract: To understand the main orographic and non‐orographic sources of gravity waves (GWs) over South America during an Experiment (Rapp et al., 2021, https://doi.org/10.1175/BAMS-D-20-0034.1 ), we propose the application of a rotational spectral analysis based on methods originally developed for oceanographic studies. This approach is deployed in a complex scenario of large‐amplitude GWs by applying it to reanalysis data. We divide the atmospheric region of interest into two height intervals. The simulations are compared with lidar measurements during one of the flights. From the degree of polarization and the total energy of the GWs, the contribution of the upward and downward wave packets is described as a function of their vertical wavenumbers. At low levels, a larger downward energy flux is observed in a few significant harmonics, suggesting inertial GWs radiated at polar night jet levels, and below, near to a cold front. In contrast, the upward GW energy flux, per unit area, is larger than the downward flux, as expected over mountainous areas. The main sub‐regions of upward GW energy flux are located above Patagonia, the Antarctic Peninsula and only some oceanic sectors. Above the sea, there are alternating sub‐regions dominated by linearly polarized GWs and sectors of downward GWs. At the upper levels, the total available GW energy per unit mass is higher than at the lower levels. Regions with different degrees of polarization are distributed in elongated bands. A satisfactory comparison is made with an analysis based on the phase difference between temperature and vertical wind disturbances. Plain Language Summary: Atmospheric gravity waves (GWs) are of great importance in the transport of energy and momentum through the atmosphere. Their sources can be broadly classified as stationary and non‐stationary. The southern tip of South America represents one of the most important natural laboratories for detecting the coexistence of large‐amplitude GWs. We present a spectral method to establish a semi‐quantitative classification of the different groups of GWs and their main vertical direction of propagation. We apply the method on the basis of global model data. We divide the lower and middle atmosphere into two vertical intervals and compare the model with data from one of the instruments deployed during the experiment. Based on the direction of rotation of the vector defined by the GW oscillations of the two horizontal wind components, we describe the net contribution of the upward and downward wave packets as a function of their spectral harmonics. The main sub‐regions of upward GW energy flux alternate with sub‐regions dominated by linearly polarized GWs and downward GW sectors mainly above the ocean. At the upper levels, the total available GW energy per unit mass is higher than at the lower levels. A comparison is made between these results and an independent analysis based on the known polarization relations for GWs. Key Points: A rotary spectral analysis is proposed to classify possible sources of gravity waves (GWs) according to their degree of polarization From reanalysis data, the method is applied at a selected position during one of the flights of the SOUTHTRAC‐GW Experiment Upward and downward GW structures from orographic and non‐orographic origin with different degrees of polarization are observed